Migraine with aura and silent brain infarcts lack of mediation of patent foramen ovale. Issue 12 (20th July 2013) - Calviere, L.; Tall, P.; Massabuau, P.; Bonneville, F.; Larrue, V.
Abstract : Background and purpose: Population‐based studies have shown a heightened prevalence of clinically silent brain infarcts in subjects who have migraine with aura (MA). We sought to determine whether this association could be confirmed in young patients with cryptogenic ischemic stroke, and explored the role of patent foramen ovale (PFO) as a potential underlying mechanism. Methods: Patients were selected from a registry of young patients consecutively treated for ischemic stroke in a tertiary university hospital among those without definite cause of stroke. Patients with PFO were matched for age and gender with patients with normal atrial septum. Migraine and MA were evaluated after patient selection and matching. Silent brain infarcts were independently evaluated on MRI. Results: We included 100 patients [60 men; mean age (SD), 44.8 years (8.3)], 50 patients with PFO. We found silent brain infarcts in 36 patients and MA in 13 patients. MA was more frequent in patients with silent brain infarcts than in patients without silent brain infarcts (25.0% vs. 6.3%; OR, 5; 95% CI, 1.4–17.6; P = 0.01). Traditional cardiovascular risk factors were not associated with silent brain infarcts. PFO was neither associated with MA (OR, 1.7; 95% CI, 0.5–5.3) nor silent brain infarcts (OR, 0.7; 95% CI, 0.3–1.5). The association of MA with silent brain infarcts was not altered after adjustment for PFO. Conclusion: Findings suggest that silent brain infarcts in young patients with cryptogenic stroke is associated with MA. We found no evidence for a mediating effect of PFO on this association.